Формування мікросудинних ускладнень у хворих із повільно прогресуючим автоімунним діабетом дорослих - Тихонова, Т. М. (Clinical Endocrinology and Endocrine Surgery, 2014)
The examination of 261 patients with slowly progressive autoimmune diabetes of adults (LADA), diabetes mellitus type 1 and 2 with an average duration of disease 3,41±0,13 years not found a significant difference in the frequency of non-proliferative and preproliferative retinopathy, as well as microalbuminuria. Expressed microvascular complications (proliferative retinopathy, proteinuric stage of nephropathy) were detected only in patients with slowly progressive autoimmune diabetes of adults. In these patients an association was established reliable relationship between the development and progression of nephropathy and retinopathy. The factors influencing the development of retinopathy in these patient were defined as the time from the onset of complaints and the time since diagnosisis was established, and the time of until insulin prescription as from the time of the first complaint, and after diagnosis establishment. In the case of diabetic retinopathy development the effect of these factors on the progression of this complication disappears.